The Role of Information Technology and Organizational Culture in Improving Employee Performance - Very M, Mufti Rosyid; Hermawan, Sigit; S Sriyono (SAGA: Journal of Technology and Information System, 2024)
This research dives into the complex dynamics between information technology, organizational culture, and employees at bfreshgigi, a dental health company that is transforming in the digital era. Through in-depth interviews with six employees from various positions, the study reveals how information technology is not just a tool, but a fundamental game changer. Organizational culture emerged as a critical counterweight, sometimes supporting innovation, but sometimes hampered by hierarchical structures. Employee performance was found to go far beyond mere productivity, encompassing adaptability and creativity. The findings suggest that alignment between technology, culture and performance is critical; when aligned, the results are outstanding, but imbalances can trigger stress and demoralization. This study not only enriches theoretical understanding but also offers practical insights for organizations struggling with digital transformation.